Implantación de la contabilidad y determinación del costo de producción en el deportivo reina del cisne y su incidencia en la situación financiera de la empresa en el periodo noviembre-diciembre de 2015 - Torres Agurto, Tatiana Del Cisne (2017)
Cost accounting in the industry is a fundamental axis for the application of control mechanisms to the cost elements, in order to establish the total and unit costs, to determine a profit margin and to allow the owner to make the right decisions. Thus, through the present work of thesis: "Implantation of accounting and determination of the cost of production in the Deportivo Reina del Cisne and its impact on the financial situation of the company in the period November-December 2015", was organized and elaborated the necessary documentation for the application of the accounting process. In addition, the total and unit cost of the finished product was determined through the elaboration of the cost sheet. By means of the realization of the financial statements, some solvency indicators were applied that were socialized with the owner with the purpose of making known their real economic situation. In carrying out the present work it was evidenced that the economic activity performed is profitable since in determining the unit cost of the finished product, a considerable profit margin was observed and at the end of the accounting period has been obtained profit.